2008
DOI: 10.1590/s0102-09352008000100014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chondroitin sulfate and sodium hyaluronate on chondrocytes and extracellular matrix of articular cartilage in dogs with degenerative joint disease

Abstract: Samples of articular cartilage of femur, tibia and patella of 15 dogs with experimentally induced degenerative joint disease (DJD) were microscopically analyzed. Animals were distributed into three groups (n=5): the control group received no medication; the second group was treated with chondroitin sulfate and the third received sodium hyaluronate. Samples were processed and stained with HE and toluidine blue for morphological evaluation. The metabolic and proliferative activity of the chondrocytes was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
1
9
1
6
Order By: Relevance
“…As regards the control joints, the histological findings reflected the degenerative nature of this model as presence of surface cartilage irregularities and fibrillation, edema, hypocellularity alternating with hypercellular & proliferative areas and decrease of the concentration of proteoglycans characterized by the reduction of staining intensity. Such changes are observed in the DJD and were also described by [40,41]. …”
Section: Discussionsupporting
confidence: 70%
“…As regards the control joints, the histological findings reflected the degenerative nature of this model as presence of surface cartilage irregularities and fibrillation, edema, hypocellularity alternating with hypercellular & proliferative areas and decrease of the concentration of proteoglycans characterized by the reduction of staining intensity. Such changes are observed in the DJD and were also described by [40,41]. …”
Section: Discussionsupporting
confidence: 70%
“…Although studies have confirmed that parenteral administration of chondroitin sulfate stimulates chondrocytes metabolism and satisfactorily reduces the progression of articular cartilage degeneration in DAD models induced by chronic instability in dog knee (Gonçalves et al, 2008;Melo et al, 2008), the results of the present study clarify that the chondroitin sulfate in association with glucosamine, as a nutraceutical, did not promote the same stimulus in the repair of sharply induced osteochondral defects.…”
Section: Discussioncontrasting
confidence: 69%
“…The model used CCLT to induce morphological changes allowed the evaluation of this common disease, as described by Biasi et al (2005), Gonçalves et al (2008) and Melo et al (2008). The development and progression of OA occurred due to joint instability, which changed the distribution of weight on the joint (Glasson et al 2007, Herzog & Longino 2007.…”
Section: Discussionmentioning
confidence: 99%